2017
DOI: 10.1590/1806-9282.63.11.988
|View full text |Cite
|
Sign up to set email alerts
|

The analysis on the expression of gasotransmitters in early trauma patients

Abstract: Objective: Nitric oxide (NO), carbon monoxide (CO) and hydrogen sulfide (H 2 S) were endogenously-generated molecules gas. They owned important biological activity and participated in many pathophysiological processes. This study aimed to examine the levels of three gasotransmitters in the early phase of trauma patients. Method: Blood samples were collected from 60 trauma patients and ten healthy volunteers. Concentration of serum iNOS and HO-1 were analyzed by enzyme linked immunosorbent assay and plasma H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…7 It interacts with superoxide ions and produces toxic peroxynitrite that can damage cells. 4 It is also involved in neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD). 1 Conditions such as trauma, shocks, and infections produce higher levels of NO, and in the experimental sepsis model, an elevated NO concentration was observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It interacts with superoxide ions and produces toxic peroxynitrite that can damage cells. 4 It is also involved in neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD). 1 Conditions such as trauma, shocks, and infections produce higher levels of NO, and in the experimental sepsis model, an elevated NO concentration was observed.…”
Section: Introductionmentioning
confidence: 99%
“…2 Studies have revealed that gasotransmitters control the generation of adenosine triphosphate (ATP), insulin sensitivity, and metabolism of glucose and lipids, and hence abnormal production of gasotransmitters is responsible for different metabolic diseases such as diabetes and obesity. 3 Furthermore, gasotransmitters are essential signalling molecules in inflammatory reactions, 4 and can also exhibit different protective roles against oxidative stress. 1 In general, gasotransmitters have a beneficial role if produced at low concentrations but lead to toxicity at higher concentrations.…”
Section: Introductionmentioning
confidence: 99%